Prevalence and Factors Associated With Severe Depression Among Caregivers of Children With Sickle Cell Disease in Northern Uganda - Atim, Martha; Mwebesa, Ivan; Ssebowa, Andrew; Etoko, Christine Atala; Kirabira, Joseph (Research square, 2023)
Background: Depression is a mental disorder characterized by depressed mood and affects more than 300 million people globally. Caregivers of children with Sickle cell disease (SCD) experience psychosocial distress which predisposes them to depression. This study aimed to determine the prevalence of and factors associated with severe depression among caregivers of children with SCD attending a large hospital in post conflict northern Uganda. Methods: A cross sectional study was conducted at the SCD clinic of St. Mary’s Hospital Lacor. Caregivers of children aged between 0 to 17 years with SCD were interviewed using Patient Health Questionnaire-9 and socio-demographics questionnaire developed by the researchers. Bivariable analysis using chi square test and multivariable logistic regression were conducted to assess associated factors. Results: 310 participants were recruited consecutively of whom 90% were female and 10% male with mean age of 32.7 years. The prevalence of severe depression among caregivers of children with SCD at SMHL was 18.4% and was associated increasing age of caregiver (adjusted odds ratio (aO.R) =1.06, C.I = 1.02-1.10). Having more than one child (aO.R= 0.321, C.I = 0.107-0.967), and extended family type (aOR= 0.284, CI= 0.114-0.537) were protective against depression. Conclusion: The study findings indicate that a substantial proportion of caregivers of children with SCD suffer from severe depression which is mostly undiagnosed and hence untreated. Therefore, policymakers need to focus on designing strategies aimed at controlling and managing depression among caregivers of children with SCD such as routine screening.
Keywords: Depression; Sickle cell disease; Disability; Child; Adult